2012
DOI: 10.1364/ao.51.006275
|View full text |Cite
|
Sign up to set email alerts
|

Laser differential confocal radius measurement system

Abstract: A laser differential confocal radius measurement system with high measurement accuracy is developed for optical manufacturing and metrology. The system uses the zero-crossing point of the differential confocal intensity curve to precisely identify the cat's-eye and confocal positions and uses an interferometer to measure the distance between these two positions, thereby achieving a high-precision measurement for the radius of curvature. The coaxial measuring optical path reduces the Abbe error, and the air-bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The basic principle behind the advanced confocal technique uses the difference in the relative locations of the cats-eye condition (when the focal point is coincident with the apex of surface) and the confocal condition (when the focal point is coincident with the centre of curvature) as a measure of the radius of curvature [15][16][17][18].…”
Section: Measurement Principlementioning
confidence: 99%
See 1 more Smart Citation
“…The basic principle behind the advanced confocal technique uses the difference in the relative locations of the cats-eye condition (when the focal point is coincident with the apex of surface) and the confocal condition (when the focal point is coincident with the centre of curvature) as a measure of the radius of curvature [15][16][17][18].…”
Section: Measurement Principlementioning
confidence: 99%
“…When the surface map proves to be inaccurate, the measurement of wetting contact angle can be improved by using an advanced confocal technique to measure the radius directly. The basic principle behind the advanced confocal technique uses the difference in the relative locations of the cats-eye condition (when the focal point is coincident with the apex of surface) and the confocal condition (when the focal point is coincident with the centre of curvature) as a measure of the radius of curvature [15][16][17][18]. A schema is shown in figure 3.…”
Section: Measurement Principlementioning
confidence: 99%
“…Anand et al measured the ROC and other optical parameters by means of a digital holographic interferometer that compared the wavefront from the test lens with a digitally inserted plane wavefront while changing the incident angle of this digital wavefront [3]. Lawall et al incorporated concave mirror into plano-concave Fabry-Perot cavity to measure ROC by using the principle of multi-beam interference [4]. Sun et al demonstrated a differential radius-measuring system to perform high-precision ROC measurement through the interference-length measuring technology [5].…”
Section: Introductionmentioning
confidence: 99%